Uses and Gratifications of Scientific Dissemination on TikTok in Peru—A Case Study@AdrianCiencia - Bautista, Karoline Cruzado (2024)
Scientific popularization has as its main purpose the dissemination of information in an accessible manner to a lay audience, for which it is necessary for traditional methods of this practice to transition to emerging digital platforms such as TikTok. The account “@AdrianCiencia” on that platform is studied, posing the following question: What uses and gratifications do users find when consuming @adrianciencia’s content? The objective is to determine if the platform is useful for effectively disseminating scientific content. Using the uses and gratifications theory, the case is studied through semi-structured interviews with men and women between the ages of 19 and 33. The results show that the interviewed individuals were able to satisfy all categories of uses and gratifications, using the application as both an entertainment and an information-seeking tool. Finally, this work provides insight into the consumed content for future creators of scientific content who seek to venture into new social media platforms.